PENCARIAN MAKNA DIBALIK AKUNTANSI KEWIRAUSAHAAN BERBASIS KEARIFAN LOKAL - Ismail, Hanif (Jurnal Akuntansi, 2015)
This research is used inductive approach to find the essence of entrepreneurial accounting by exploring the meaning of entrepreneurial accounting on business practice in the Padang restaurant. The paradigm is interpretive with phenomenological method by involving researchers as participant observer in the study sites. The finding research is founded of significance of entrepreneurial accounting, they are: unyielding spirit, accounting creations to achieve productivity, openness, motivate each other, act fairly, and jointly owned businessesKeywords:   Accounting, Entrepreneurship, jointly owned business, fair, openness,   phenomenology, unyielding spirit